EXPLORING THE VOCABULARY LEARNING STRATEGIES OF ITALIAN LEARNERS OF ENGLISH - James Rock (Universitat Jaume I. Department of English Studies, 2019)
Author/s James Rock Università Cattolica del Sacro Cuore di Milano, Italy   ABSTRACT In this paper, a think-aloud protocol is used to explore the vocabulary learning strategies of ten adult learners of English at a university in the north of Italy. The focus is on discovering the types of actions that are actually employed by learners while performing a deliberate vocabulary learning task. As well as providing information about frequency of use, the investigation revealed some patterns of strategy use. In general, less attention was awarded to techniques involving deeper mental elaboration, such as complex guessing for meaning or the use of mnemonic techniques, in favour of strategies requiring less mental effort. There was also less emphasis on mechanical repetition than in many previous studies on the topic.